Ubatubaneura, a new genus of the Corynoneura group (Diptera: Chironomidae: Orthocladiinae) from the Brazilian Atlantic Forest - Wiedenbrug, Sofia; Trivinho-Strixino, Susana (Zootaxa, 2009)
Male, female, pupa, and larva of Ubatubaneura atlantica n. gen., n. sp. from the Brazilian Atlantic Forest are described based on specimens collected from the surface of stones in low order streams and reared in the laboratory. The adults can be separated from other members of the Corynoneura group on the right-angled dorsolateral region of the head and on the terminal flagellomere of the antenna having a triangular apex surrounded by sensilla chaetica. The pupa can be distinguished by the presence of two long, taeniate L-setae on segments III–V, the presence of only non-taeniate L-setae on segments VI–VIII, and by having three macrosetae ventrally on the anal lobe. The 5-segmented antenna of about 1/2 the length of the head, antennal blade not longer than the flagellum, bifid SI, short body setae, and apically split subbasal seta on the posterior parapod are diagnostic characters differentiating the larva from other genera. Several characters in the male, pupa, and larva indicate that Ubatubaneura has a basal position within the Corynoneura group of genera. Preliminary keys to the males, females, pupae, and larvae for most genera of the Corynoneura group are given.